Upregulation of S100A6 in patients with endometriosis and its role in ectopic endometrial stromal cells. (2nd September 2018) - Peng, Yaoming; Lin, Jiabin; Ma, Junyan; Lin, Kaiqing; Xu, Kaihong; Lin, Jun
Abstract: S100 calcium-binding protein A6 (S100A6) is up-regulated in many malignancies and overexpression of S100A6 has been identified associated with proliferation, migration and invasion phenotype in several cancer cells. In the present study, we explored whether S100A6 plays a role in the development of endometriosis. Significantly higher levels of mRNA and protein expression of S100A6 were observed in ectopic endometrial tissues compared to eutopic and normal endometrial tissues. Silencing of S100A6 in ectopic endometrial stromal cells (ESCs) significantly inhibited cell viability, migration and invasion. Moreover, knockdown of S100A6 suppressed p38/MAPK activity in ectopic ESCs, which can be partially attenuated by CacyBP/SIP phosphorylation inhibitor. In conclusion, our results suggest that the abnormal expression of S100A6 may contribute to the pathogenesis of endometriosis and the S100A6/CacyBP/p38 signaling may provide as a promising treatment target.